La ejemplificación en la gramática y la dialéctica griegas desde la lingüística de corpus. - Redondo Reyes, Pedro (Myrtia, 2025)
Greek grammarians used two types of exemplification in their treatises: those from the literary tradition and those taken from current language. The same procedure is observed in dialectics, especially that developed by Stoicism. The paper examines these uses in both disciplines and their possible consideration as an advance of modern corpus linguistics.